Tracking and risk assessment of microplastics in a wastewater treatment plant - Kamani, Hossein; Ghayebzadeh, Mehdi; Ganji, Fatemeh (Water and environment journal : WEJ, 2024)
Today, microplastics have become one of the most important environmental concerns. Wastewater treatment plants are a major source of microplastics in the environment. The aim of this study is to track and assess the risk of microplastics in a wastewater treatment plant. Samples were taken from different units of sewage treatment plants in the spring and winter. Microplastics were separated using sieves and density‐based methods. Analysis revealed a higher abundance of microplastics in spring. The highest amount of microplastic removal was in the disinfection and secondary sedimentation units in the winter season. Fragments are the most common shape. Poly Ethylene Terephthalate (PET) polymers were most prevalent. Black was the most common colour. Poly Ethylene (PE), PET and poly Amide (PA) polymers posed the highest risk, according to calculations. One of the most important ways to prevent microplastics from entering water sources is to reduce the consumption of plastic materials, recycle plastic waste and remove microplastics from the wastewater treatment process. Highlights The most common microplastic shapes observed were fragments. The most common microplastic colour observed was black. The most common polymers observed were polyethylene terephthalate. Polyethylene terephthalate, polyamide and polyethylene polymers have a high hazard risk.